Pengaruh Opini Audit, Temuan Audit, dan Karakteristik Daerah terhadap Ketepatan Waktu Laporan Keuangan Pemerintah Daerah di Sumatera - Rezi Oktawiana; Dian Fitria Handayani (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to analyze the influence of audit opinions, audit findings, and regional characteristics on the timeliness of local government financial reports in Sumatra in 2021. This research uses a quantitative approach. Sampling method using Purposive based on predetermined criteria and produced sample 90 local governments in Sumatra in 2021. Multiple regression analysis was employed to test the hypothesis. The results shows that audit opinions and local government measures have negative effect on LKPD timeliness, while the findings audit and the age of the local government have no effect on the timeliness of LKPD.